Microplastics in environmental setting: a review on sources, exposure routes and potential toxicities on human health - Sulong, Nor Azura; Mohamed, Noradila; Abd Ghani, Fazni Susila; Sulong, Ahmad Hanafi (Universiti Teknologi MARA (UiTM), 2024)
Microplastics are pervasive throughout various ecosystems, but the potential risk of exposure to humans remains uncertain. Microplastics are plastic particles measuring less than five millimeters, and they infiltrate ecosystems via soil, water, atmosphere and living organisms where they are potentially impacting human health. The sources, routes of exposure, and potential effects on human health are reviewed in the current paper. Microplastics are regularly identified in both environmental and human specimens. They can be found in roadside dust, indoor air, fresh and surface water, beverages, honey, sugar, and other dietary items. Microplastics can enter the human body through the skin, food, or inhalation and may have negative health impacts. A significant challenge in assessing the potential health risks posed by microplastics is the lack of data regarding human exposure. There is an urgent need for effective analytical instruments capable of sampling, isolating, detecting, quantifying, and characterizing microplastics. The objective of the paper is to summarize the literature on the sources, distribution, route of exposure and the potential toxicities of microplastics and to identify the research gap for the future work. We searched for hundreds of papers related to microplastics from 2013-2023. We then screened them for inclusion, evaluated the quality of the study, extracted the data and conducted the data analysis. We provide a summary of the harmful effects of microplastics on animals, organoids, and cell models used in experiments. Microplastics have been linked to immunotoxicity, neurotoxicity, metabolic disorders, and reproductive toxicity. Finally, we provide future perspectives on the prevalence, characterization, fate, and breakdown of microplastics as they are needed for gaining a comprehensive understanding of microplastics. This review provides a concise overview of the sources, pathways through which humans are exposed to microplastics and potential toxicity effects of microplastics